Supporting transgender and non-binary students and staff in further and higher education practical advice for colleges and universities - Lawrence, Matson; McKendry, Stephanie (Jessica Kingsley Publishers, 2019)
"According to the research underpinning this book, 85% of trans students and staff faced barriers. This practical guide enables post-secondary education professionals to create a safe and supportive environment for gender diverse applicants, students and staff. Using real-life examples to explore common experiences and challenges for trans people in further and higher educational settings, it sets out policies, interventions and advice that have proven effective in providing impactful support on a wide range of issues such as learning, teaching, mental health, recruitment, support services, and institutional policies. Included is an easy-to-follow introduction to transgender terminology and identities, as well as legal and medical considerations"--Provided by publisher.